From ivory tower to academic commitment and leadership : the changing public mission of universities - Oliver, Amalya; Drori, Gili S. (Edward Elgar Publishing, 2021)
"How is the public mission of universities to change in the face of today's global challenges? How is the 21st Century university to balance its long-standing traditions and its commitment to teaching, research and commercialization with rapidly changing social needs and conditions worldwide? And how does the newly defined public role of the university reflect on changes to non-profit organizations in general? Amalya Oliver-Lumerman and Gili S. Drori offer a new model of academic commitment and leadership in response to questions about the new public role of the university. Combining historical and sociological analysis with examples and proposals for academic commitment and leadership, the book reconsiders the social impact of universities and, by extension, public organizations. It offers detailed examples for Academic Leadership and Responsibility (ACL) programs and related projects, contributing to higher education policy-making and discussions around university governance. In exploring the changing public mission of universities, the book also highlights models of social responsibility and leadership that are appropriate for universities, and discusses the translation of CSR to a non-profit public organization. This will be an invigorating read for higher education and organization studies scholars, as it engages with current debates about the future of university models and public sector organisational forms"--